PERSEPSI DAN PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN LUMBUNG PANGAN DI KABUPATEN LAMPUNG BARAT - Kholik Kholik; Hardinsyah Hardinsyah; M. Djemdjem Djamaludin (Jurnal Gizi dan Pangan, 2008)
Community’s perception and participation is necessary to be noticed in the effort of developing food barn in rural area. The objective of this study were to: 1) analyze community’s perception about food barn in Lampung Barat District, 2) inventory factors that influence community’s participation in developing food barn in Lampung Barat District, 3) formulate model and strategy in developing participative food barn to reach food security in Lampung Barat District. This research was conducted by using cross sectional design and descriptive analysis approach. The location was chosen by using purposive sampling which were in Tribudi Syukur Village, Sumberjaya Subdistrict and Buay Nyerupa Village,  Sukau Subdistrict. The selection was based on consideration that these villages has different implementation performance of food barn according to the assessment from Food Crops and Horticulture Office in Lampung Barat District. The result of the research shows that the community’s perception category, represented by farmer as sample, based on total perception variable score between Tribudi Syukur and Buay Nyerupa, is different. The general condition of the community (like age, education level, income, etc.) do not have correlation with its perception about food barn. The community’s participation in food barn category, represented by farmer as sample, based on total participation variable score between Tribudi Syukur and Buay Nyerupa, is also different. There is correlation between community’s perception about food barn and its participation in developing food barn activity. The factors that influence community’s participation in developing food barn are tradition to store food by the community, the existence of farmer group, community’s perception about food barn, the existence of regional governmental structural institution in Food Security, regulation or guidance which support food barn developing, governmental program which support food barn development, the development of food market and trading, condition of region which potentially food insecure. The priority of strategy in developing participative food barn based on the result of SWOT analysis that possible to be conducted are 1) develop community’s perception to not relying on market in accessing food, 2) develop perception and community participation empowerment in creating and developing food barn based on regional condition, 3) maintain and build community’s tradition of storing food from self food storing to collective food storing (in group).